2020
DOI: 10.13106/jafeb.2020.vol7.no7.251
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Total Factor Productivity, and Institution Quality in Low-Middle Income Countries in Asia

Abstract: The purpose of this paper is to investigate the impact of total factor productivity (TFP), institutional quality, and interactive variable between them on economic growth in 13 low-middle income countries in Asia for the period 2000-2018. The paper uses the difference Generalized Method of Moments (GMM) to explore the dataset provided by the World Bank. The empirical results show that TFP and the interactive variable positively impact on the economic growth, while the institutional determinants have a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…In recent years there are many domestic and foreign scientific studies in this field. Nakabashi et al (2013), Alexiou et al (2014), Acemoglu et al (2014), Vianna and Mollick (2018), Salman et al (2019), Ha (2016), Ngo and Nguyen (2020) concluded that institutions have positive impacts on economic growth. However, Dias and Tebaldi (2012) and Acemoglu et al (2015) did not find a relationship between institutions and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there are many domestic and foreign scientific studies in this field. Nakabashi et al (2013), Alexiou et al (2014), Acemoglu et al (2014), Vianna and Mollick (2018), Salman et al (2019), Ha (2016), Ngo and Nguyen (2020) concluded that institutions have positive impacts on economic growth. However, Dias and Tebaldi (2012) and Acemoglu et al (2015) did not find a relationship between institutions and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In a study for Nigeria, Olanrewaju, Tella and Adesoye (2019) used augmented VAR to show that all the variables used in the study, except the financial inclusion index Granger-caused growth without feedback. For Asian countries, Ngo and Nguyen (2020) use the GMM to show that institutional factors do not have a positive impact on economic growth in middle-income countries.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Increasing productivity in individual countries by increasing the efficiency of capital, labour and other inputs is one of the appropriate solutions in the current situation. It can be seen that growth research is still the subject of interest and discussion among researchers (Ngo and Nguyen 2020). The relationship between labour productivity and economic growth was also analyzed by Rey and Hazem (2020).…”
Section: Literature Reviewmentioning
confidence: 99%